Data managers: A survey of the European Society of Breast Cancer Specialists in certified multi‐disciplinary breast centers. Issue 5 (23rd April 2018) - Schnapper, Gabriele; Marotti, Lorenza; Casella, Denise; Mano, Maria P.; Mansel, Robert E.; Ponti, Antonio
Abstract: The European Society of Breast Cancer Specialists( EUSOMA) requires that the breast centers' core team includes a trained person responsible for data collection and analysis. We addressed a questionnaire to the data managers of the EUSOMA breast centers network in order to acquire information with regard to their education, training, role, activity, recognition, and satisfaction. Breast centers' data managers are highly educated individuals with a variety of backgrounds carrying out, more frequently part‐time and as temporary employees, a job for which they received little specific training. These findings support the importance of defining a core curriculum and a training program.